Meningkatan Kemampuan Komunikasi Siswa Vokasi Menggunakan Flipbook dengan Augmented Reality - Dhahrani, Jasmine Al; Rahayu, Sri; Suryadi, Dedy (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
The era of society 5.0 today plays an important role in everyday life, especially in education, which requires learning innovation. This research aims to develop learning innovations for an effective society in the 5.0 era. The method used to test the validity of flipbook learning media with AR is ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The results of the study showed that the educational media is valid, with a score of 80,5% for the material experts and 80,8% for the media experts.